The association between circulating short-chain fatty acids and blood pressure in Chinese elderly population - Jiamou Zhou; Heqiao Zhang; Pengcheng Huo; Huiyan Shen; Qian Huang; Linsheng Yang; Annuo Liu; Guimei Chen; Fangbiao Tao; Kaiyong Liu; Dongmei Zhang (Scientific Reports)
Abstract The gut microbiome primarily generates short-chain fatty acids (SCFAs) by fermenting dietary fibers. Though previous studies have linked SCFAs to blood pressure, there remains a lack of research on the relationship between SCFAs levels in the serum of elderly individuals and blood pressure. Based on this, we investigated the associations of serum SCFAs with blood pressure in Chinese older adults in a cross-sectional study. In this report, we recruited 1013 older adults over 60 years of age from June to September 2016 in Lu 'an City, China. Using Ultra High Performance Liquid Chromatography-Quadrupole-Exactive-Orbitrap-Mass Spectrometry (UHPLC-QE-Orbitrap MS), we measured the level of various SCFAs, including acetic acid (AA), propanoic acid (PA), butyric acid (BA), isobutyric acid (iso-BA), valeric acid (VA), isovaleric acid (iso-VA), and caproic acid (CA), in serum samples collected from Chinese elderly adults. The study recruited 1013 older adults in total. Multiple logistic regression analysis shows that AA (OR = 0.696, 95%CI: 0.501–0.966) and VA (OR = 0.713, 95%CI: 0.516–0.985) are negatively associated with hypertension. Linear regression analysis shows a negative correlation between AA (β = -3.89, 95% CI: -7.12 – -0.66) and the systolic blood pressure (SBP) levels, and a significant negative association between iso-VA (β = -2.11, 95% CI: -3.94 – -0.29) and diastolic blood pressure (DBP) levels. Whether in unadjusted or adjusted linear regression models, we all observe significant positive associations between CA and blood pressure levels. In the Bayesian kernel-machine regression (BKMR) models, the trends between the mixture of SCFAs and hypertension, SBP are inverse, but not significant; we also observe a significant negative correlation between AA and SBP, and a significant negative association between iso-VA and DBP levels, while CA is significantly positively correlated with SBP and DBP. Collectively, our results advocate for considering SCFA as a potential intervention to lower blood pressure, and especially AA may be a possible target for research. This may provide new perspectives for understanding the role of SCFAs in hypertension.